PEMBIYAAN PENDIDIKAN MELALUI SEKTOR ZAKAT BADAN AMIL ZAKAT KABUPATEN ROKAN HULU - Syukri Rosadi (HUKUMAH: Jurnal Hukum Islam, 2020)
This study aims to find out how educational financing program is done, to know thecriteria of students who will get educational scholarship, and to know the flexibility inallocating zakat funds for education at the bazanas kabupaten rokan hulu. This researchuse desciptive qualitative approach. Methods of data collection in this study was conductedby observation, interview, and documentation. Data analysis techniques in this study usinginteractive data analysis techniques consisting of three components of data analysis that isdata reduction, data presentation, and conclusion. The results of this study found there aretwo educational financing programs undertaken by this institution is an integratedscholarship program and orphaned pesantren. Both programs are financed from the utilization of zakat funds that have been collected. The criteria of the studentsreceiving educational scholarships are classified by priority scale: 1) the poor, orphan,takmir mosque; 2) the poor, orphans; 3) the poor. In addition there is the flexibility of thebudget in allocating zakat funds for education programs